Retrospective analysis of the relationship between bone mineral density and body composition in a health check-up Chinese population - Li, Yuxin; Huang, Zhen; Gong, Yan; Zheng, Yansong; Zeng, Qiang (Frontiers in Endocrinology, 2022)
Purpose: This study was designed to explore the relationship between bone mineral density (BMD) and body composition indicators in Chinese adults (≥50 years) in order to provide a scientific basis for optimal bone health management. Method: Individuals ≥50 years old who received physical examinations and routine check-ups at the Health Management Research Institute of PLA General Hospital from September 2014 through March 2022 were included as research subjects in this study. Basic clinical and demographic information were recorded for all subjects, along with smoking and drinking status, height and body weight. A panel of routine blood chemistry and metabolite markers were measured, along with lean muscle mass and body fat mass using body composition bioelectrical impedance analysis (BIA). Body mass index (BMI), body fat percentage (BFP), skeletal muscle mass index (SMI), and bone mineral density (BMD) were calculated for all individuals. For comparative analysis, individuals were grouped based on their BMI, BFP, SMI and BMD T-score. Follow-up examinations were performed in a cohort of 1,608 individuals matched for age, sex, smoking and drinking history for ≥5 years, Results: In this large cross-sectional study, age, smoking, homocysteine (Hcy) and blood glucose levels were established as independent risk factors for osteoporosis. Multi-factor logistic regression analysis showed that age, sex, BMI, intact parathyroid hormone (iPTH), SMI, BFP, smoking, blood levels of inorganic phosphate (P) and K+ were all significantly associated with osteoporosis risk (P<0.05). A subset of these factors- BMI, SMI, BFP and K+, were determined to be protective. In the cohort followed for ≥5 years, SMI and BMD decreased while BFP and BMI increased significantly (P<0.001) over time. Conclusion: Risk of osteoporosis may be reduced by increasing body weight, particularly lean muscle mass, while simultaneously controlling BFP.